ACUTE MYELOMAL ENTEROCOLITIS IN A PATIENT WITH FIRST-TIME DIAGNOSIS OF ACUTE LEUKEMIA - Rudaeva, Elena Vladimirovna; Elgina, Svetlana Ivanovna; Fetishcheva, Larisa Egorovna; Moses, Kira Borisovna; Moses, Vadim Gelievich (Medicine in Kuzbass, 2026)
The article describes a clinical case of fatal acute myeloid enterocolitis in a patient with newly diagnosed acute leukemia. Acute myeloid enterocolitis (AME), also known as typhlitis or neutropenic enterocolitis, is one of the most severe complications in patients with hematological malignancies, particularly acute leukemias. This condition is characterized by transmural inflammation of the intestinal mucosa, primarily in the cecum, accompanied by severe neutropenia. The disease rapidly progresses to perforation, peritonitis, and sepsis, with extremely high mortality rates. This clinical case clearly illustrates the diagnostic difficulties and fatal course of OME in a young patient.
Keywords: acute myelomatous enterocolitis; acute leukemia